Fitting a woven-cloth model to a curved surface: mapping algorithms - Aono, M.; Breen, D.E.; Wozny, M.J. (Computer aided design, 1994)
The problem of fitting a 2D broadcloth composite ply (modelled as a piece of deformable woven cloth) onto a 3D curved surface (modelled with a NURBS surface) is considered. ‘Fitting’ means that a ply is deformed and applied to a surface so that it is everywhere in contact with the surface. A fitting method is presented that incorporates a flexible method for specifying initial conditions, and allows for the simulation of a wide range of fitting configurations.